Evaluation of several methods for breakind dormancy of bitter vetch seeds (Vicia Ervilia L.) - Sepehri , Ali; Rouhi, Hossein Reza; Sefidkhani, Leila (Plant Breeding and Seed Science, 2015)
This study analysed the effects of different treatments on breaking dormancy and germination of bitter vetch (Vicia ervilia L.) freshly harvested seeds for seeding immediately. Partial scarified seeds (30 seconds with sandpaper) were subjected to different treatments including: GA3 (250, 500 and 750 ppm), KNO3 (0.1, 0.2 and 0.3% w/v), cold stratification (2, 4 and 6 days), sulfuric acid (25, 50 and 75 seconds), hot water (90°C; for 2.5 and 5 minutes), hydropriming via seed soaking in distilled water (4 and 8 hours) and mechanical scarification. Among the mentioned treatments, cold stratification for 6 days had a best effect on germination related parameters final germination percentage, mean germination time and vigour index than the other periods. In contrast to scarification with acid and hot water, mechanical scarification improved germination parameters but this effect was lower than the cold stratification. The results suggest that bitter vetch seed has both physical and physiological dormancy.